2023
DOI: 10.4037/ccn2023317
|View full text |Cite
|
Sign up to set email alerts
|

Use of Female External Urinary Catheters in a Burn Intensive Care Unit: Benefits and Challenges

Abstract: Background Burn patients have a relatively high rate of indwelling Foley catheter use because of their need for complex fluid management and wound care. However, Foley catheter use is associated with risks, including urinary tract infection. For female patients, an external urinary catheter is an alternative. Objectives To evaluate the use of female external urinary catheters in a burn intensive care unit and to develop a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Skin Complications 8 20,23,25,30,34,38,42,65 3 studies reported erythema and skin breakdown due to device firmness, high suction, or allergic reaction to device material. 1 study found that hospital-associated pressure injuries (HAPIs) nonsignificantly increased after FEUWD implementation.…”
Section: More Data Neededmentioning
confidence: 99%
“…Skin Complications 8 20,23,25,30,34,38,42,65 3 studies reported erythema and skin breakdown due to device firmness, high suction, or allergic reaction to device material. 1 study found that hospital-associated pressure injuries (HAPIs) nonsignificantly increased after FEUWD implementation.…”
Section: More Data Neededmentioning
confidence: 99%